Ghosts and Shadows : House of Shadows - Book 1 - Coates, Darcy (Naperville, Illinois : Poisoned Pen Press, 2020)
"Sophies world is shattered when disaster bankrupts her family. Marrying the mysterious Mr. Argenton may restore her familys fortunes and save them from scandal, but it condemns Sophie to a life in Northwood, a vast and unnaturally dark mansion situated hours from civilization. Still, she must do her duty. As time passes, Sophie struggles to adjust to her new position as mistress over the desolate house. Mr. Argentons relatives are cold, and Mr. Argenton himself is keeping secrets. Even worse, the house is more than it seems..."--
"Originally self-published in 2016 by Black Owl Books."
Keywords: Husband and wife -- Fiction; Haunted houses -- Fiction; Gothic Horror fiction; Gothic fiction; Ghost stories; Australian fiction -- 21st century